Upaya Peningkatan Aktivitas dan Hasil Belajar Murid melalui Model Discovery Learning Berbantuan Bamboozle pada Materi Stoikiometri Kelas X.1 SMA Negeri 12 Pekanbaru - Deprimasyah Deprimasyah; Roza Linda; Sri Haryati (Lembaga Yasin AlSys, 2026)
The low learning activity and cognitive learning outcomes of Class X.1 students at SMA Negeri 12 Pekanbaru on stoichiometry formed the basis for conducting this study, particularly because teacher-centered learning caused students to be less active in asking questions, discussing, and independently constructing conceptual understanding. This study aims to improve students’ learning activity and cognitive learning outcomes through the implementation of the Discovery Learning model assisted by Bamboozle media. This study used the Classroom Action Research (CAR) method, which was implemented in two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. The research subjects were 40 students of Class X.1 at SMA Negeri 12 Pekanbaru. Data were collected through observation of learning activity, learning outcome tests, and documentation, then analyzed descriptively and quantitatively. The results showed that students’ learning activity increased from 45.05% in Cycle I to 52.61% in Cycle II. Cognitive learning outcomes also improved, as indicated by an increase in the average score from 76.00 in Cycle I to 83.00 in Cycle II, while classical learning mastery increased from 37.5% to 80%. The conclusion of this study affirms that the implementation of the Discovery Learning model assisted by Bamboozle media can improve students’ learning activity and cognitive learning outcomes on stoichiometry. The implications of this study indicate that integrating student-centered learning models with game-based media can serve as an effective, interactive, and enjoyable alternative for chemistry learning.